Métodos de obtenção e caracterização de concentrado proteico de tortas de crambe - Santos , Felipe samways (2019)
This trial aims at establishing an extraction method of crambe cake protein concentrate, which was developed in two steps, at LACON, at the Western Paraná State University - campus of Cascavel. During the first phase, protein concentrate extraction was obtained according to the following methods: IA - protein solubilization with defatted press cake; IB - protein solubilization with the whole press cake; II - isoelectric precipitation; III - alcoholic extraction. The isoelectric precipitation method showed the highest content of protein in concentrate (75.65%). The solubilization and alcoholic extraction showed a bit more than 40%. The highest yields of protein concentrate and protein extraction yield were obtained by the solubilization method with the whole and defatted press cakes. The amount of tannins in concentrate obtained by alcoholic extraction was 577.86 mg kg-1, statistically lower than 916.75 mg kg-1 in the press cake. And this was the sole applied method, capable of decreasing this compound on step I. On the second phase, the isoelectric precipitation method was the only one applied, and the objective was to obtain protein concentrates from stored and defatted press cakes. The protein extraction yield of a pressed cake without storage was 62.75%, while the protein concentrate yield was 33.63%. The protein concentrates obtained from cakes without storage, and stored for 1 to 3 years were, respectively, 79.32; 73.44 and 72.04% protein. Water absorption capacity of the studied concentrates decreased due to the cakes storage, as well as oil absorption capacity. It was recorded that there was a little decrease of protein solubility during cake storage. And concerning the concentrate’s color, it was visually observed some trend to the brown color. However, parameters such as L*, b* and c* presented significant differences and indicated the darkening of a concentrate due to the pressed cakes storage time. Tannins decreased in protein concentrates obtained off press cakes stored for 1 and 3 years, when this variable was compared to the amount present in the studied cakes. Although, it was not observed any decrease in the pressed cake concentrate without storage.